Short-term high-fat diet affects macrophages inflammatory response, early signs of a long-term problem - Ed Wilson Santos; Dalila Cunha Oliveira; Araceli Hastreiter; Graziela Batista Silva; Jackeline Soares de Oliveira Beltran; Marcelo Macedo Rogero; Ricardo Ambrósio Fock; Primavera Borelli (Universidade de São Paulo, 2019)
Obesity is a chronic inflammatory disease that affects millions of people worldwide. Most studies observe the effects of a high-fat diet (HFD) in 10-12 weeks. This work investigated the effects induced by a HFD administered for 6 weeks on the nutritional status of mice and some aspects of the inflammatory response in mouse peritoneal macrophages. Male Swiss Webster mice, 2-3 months of age, were fed a control diet or HFD for 6 weeks. After this period, the mice were euthanized, and peritoneal macrophages were collected for immunoassays and assessment of biochemical parameters. A HFD was associated with increased cholesterol, insulin resistance, C-reactive protein (CRP), leptin, and serum resistin levels. Lipopolysaccharide (LPS)- stimulated adipocyte cultures of animals subjected to a HFD showed increased production of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6). However, peritoneal macrophages of the HFD group showed no changes in the levels of these cytokines. LPS-stimulated peritoneal macrophages from HFD-treated animals showed a reduction in mRNA expression of TNF-α and IL-6, as well as a decrease in expression of the transcription factor nuclear factor-kappa B (NF-kB). In conclusion, HFD treatment for 6 weeks induces similar signs to metabolic syndrome and decreases the capacity of peritoneal macrophages to develop an appropriate inflammatory response to a bacterial component.